Bọlanle Awẹ: The Matriarch of Feminist History - Toyin Falola (Yoruba Studies Review)
At the celebration of the 70th anniversary of the founding of the University of Ibadan, famous historian, Professor Bọlanle Awẹ was conferred with a well-deserved honorary doctorate degree. For both Professor Awẹ and even Nigeria’s premier university, this great honor is a fitting tribute to mark the anniversary of the institution of learning that has been central to the intellectual history of Nigeria. The University of Ibadan has done well to select Professor Awẹ for this honor. Her earnestness and intelligence are beyond doubts. There is no gainsaying disputing her warmth, her magnetism. I have known her since the 1970s—she remains consistent in the exhibition of positive values, in the promotion of Yoruba culture, and the advancement of the scholarly enterprise.